LAW ENFORCEMENT'S RESPONSE TO THE CRIMINAL ACT OF HEALTH QUARANTINE UNDER LAW NUMBER 6 OF 2018 - Suyanto, Dr (SYNTIFIC, 2025)
Background. Article 9 and Article 93 of Law Number 6 of 2018 state that non-compliance with quarantine or social restrictions may result in punishment for not participating in preventing virus outbreaks, aimed at preventing public health emergencies. This research purpose to explained law enforcement oppose the criminal act of enforcing health quarantine. Research Methods. This study employs normative and empirical legal methodologies. The data used is secondary. Data obtained through qualitative analysis. The data analysis results can be expanded upon by drawing inductive conclusions. Findings. It demonstrates that law enforcement uses criminal law facilities (ultimum remidium) to combat the criminal act of implementing health quarantine in accordance with Law Number 6 of 2018 concerning Health Quarantine. This is done by pursuing legal remedies against those who commit crimes related to organizing health quarantine through court proceedings. return in order to obtain criminal penalties and guarantee legal certainty, based on the terms of legislative rules all the way down to the court level and execution. Conclusion. Based on Law Number 6 of 2018 concerning Health Quarantine, the government and law enforcement officials can enhance the professionalism and integrity of law enforcement against the criminal act of implementing health quarantine in order to suppress those who commit such crimes.